Reading and Writing Research Based on Surname Group - Liu, Jiexuan (Journal of Biology and Life Science, 2024)
This study examines the influence of surname on academic performance in higher education. It includes an in-depth analysis of comprehensive book circulation data from the library of Nanjing Normal University, covering the period from 2012 to 2023. The study uses Kendall coefficients to assess the consistency in book circulation and renewal among the top 300 surnames of readers, employs multidimensional scaling analysis to identify differences or similarities between categorical variables through direct distance assessment, uses chi-square tests to measure the correlation between surnames above and below the mean line and various categorical variables, and conducts survival analysis to examine circulation activities related to the top 300 surnames. Results are interpreted in the context of female-dominated education and teacher preparation. The results reveal a consistent pattern in the 12-year borrowing and renewal habits of the top 300 surnames of readers. A hierachical mismatch between the reader, book category, and author reflects complex reading interests beyond academic authority. In the wake of the COVID-19 pandemic, readers with surnames above the average have shown less interest in using the book renewal service. The borrowing and renewal activity for the disappeared surnames changed within two years for foreign language books and six years for Chinese books.